Penguatan Karakter Santri melalui Sosialisasi Preventif Perilaku Menyimpang Berbasis Nilai-Nilai Kepesantrenan di Pondok Pesantren Sunan Drajat Lamongan - Nashihin Nashihin; Siswadi Siswadi; Muhyidin Muhyidin (Santri : Journal of Student Engagement, 2026)
Adolescence is a very important developmental phase characterized by significant physical, psychological, and social changes. At this stage, adolescents are vulnerable to deviant behavior due to the process of self-identity search and the influence of the surrounding environment. This community service activity aims to increase students' understanding and awareness of deviant behavior through socialization activities at the Sunan Drajat Lamongan Islamic Boarding School The method of implementing this community service activity is carried out through an educational-participatory approach consisting of several stages, namely: (1) the preparation stage, including identifying partner needs, coordination with the manager of the Sunan Drajat Islamic Boarding School, and the preparation of socialization materials; (2) the implementation stage, in the form of delivering material on the prevention of deviant behavior, strengthening the character of students, interactive discussions, and question and answer sessions; and (3) the evaluation stage, which is carried out through observation of participant participation, reflective discussion, and submission of feedback to determine the level of understanding of the students to the material provided. This approach aims to increase the knowledge, awareness, and commitment of students in applying character values and avoiding deviant behavior in the pesantren environment.with a participatory model through observation, interactive lectures, group discussions, and simple evaluations. The participants of the activity amounted to 45 students aged 15-18 years. The socialization material includes the definition of deviant behavior, its forms, causative factors, and its impact on individuals and the social environment The results of the activity show that students participate in the entire series of socialization with enthusiasm, actively participate in discussion and question and answer sessions, and are able to identify various forms of deviant behavior and their prevention efforts based on the material that has been delivered. Before the activity, the understanding of the students was still limited to violating the rules of the pesantren. However, after the activity, students were able to explain the concept of deviant behavior more comprehensively, identify the causative factors, and understand the impact. An interactive and participatory approach has been shown to be effective in increasing participant engagement and understanding. In conclusion, this socialization activity is an effective preventive strategy in suppressing the potential for deviant behavior in adolescents in the pesantren environment. It is necessary to have a sustainable implementation and collaboration between educators and Islamic boarding schools to strengthen the character formation of students.